Endogenous endothelium-derived relaxing factor opposes hypoxic pulmonary vasoconstriction and supports blood flow to hypoxic alveoli in anesthetized rabbits. - Sprague, R S (1992)
Agents that inhibit nitric oxide synthesis augment hypoxic pulmonary vasoconstriction. In an animal model of unilateral alveolar hypoxia, we investigated the hypothesis that endogenous endothelium-derived relaxing factor/nitric oxide opposes hypoxic pulmonary vasoconstriction and supports blood flow to hypoxic alveoli, resulting in a reduction in arterial oxygen tension (PO2). In pentobarbital-anesthetized rabbits, unilateral alveolar hypoxia was produced by ventilation of one lung with 100% oxygen and the other with 100% nitrogen (O2/N2). NG-Nitro-L-arginine methyl ester (0.03 followed by 1.0 mg/kg i.v.) resulted in dose-dependent decreases in the percent of pulmonary blood flow to the N2-ventilated lung and increases in arterial PO2. L-Arginine (1 mg.kg-1.min-1 i.v.) prevented the NG-nitro-L-arginine methyl ester-induced redistribution of blood flow away from hypoxic alveoli and improvement in arterial PO2. Indomethacin (5 mg/kg i.v.) administered during O2/N2 ventilation resulted in a reduction in the percentage of total blood flow to the hypoxic lung and an increase in arterial PO2. However, NG-nitro-L-arginine methyl ester administered in the presence of indomethacin caused additional diversion of blood flow away from the hypoxic lung. The magnitude of the changes suggests that the endothelium-derived relaxing factor/nitric oxide system has the capacity to make a greater contribution than products of cyclooxygenase-mediated arachidonic acid metabolism in supporting blood flow to hypoxic alveoli in the rabbit.